Dual-Positive CD4/CD8 Primary Cutaneous Peripheral T-Cell Lymphoma Previously Classified as Mycosis Fungoides a Tumor D'Emblée. (November 2018) - Raychaudhuri, Sreejata; Rahvar, Maral; Jedrych, Jaroslaw; Karunamurthy, Arivarasan; Kruglov, Oleg; Rakfal, Susan; Kane, Kevin; Akilov, Oleg E.
Abstract : Abstract: Cutaneous peripheral T-cell lymphoma, not otherwise specified represents a "waste basket" of all cases that cannot be put into another of the categories of mature cutaneous T-cell lymphoma. Previously, the sudden multifocal development of cutaneous CD4 + tumors without preceding a patch or plaque stage was classified as d'emblée form of mycosis fungoides (MF). Currently, the term "MF" reserved only for the classic Alibert–Bazin type characterized by the evolution of patches, plaques, and tumors or for variants showing a similar clinical course. The authors describe a 75-year-old white woman who presented with a solitary skin tumor in the right supraclavicular region, with no lymph node or systemic involvement. Local external beam radiation treatment resulted in a complete response. The patient relapsed after 5 months with new tumors in the left neck and left upper chest. Biopsy of the lesions showed a dermal infiltrate of atypical small- to medium-sized T-lymphocytes, and immunohistochemical staining showed coexpression of CD4/CD8 in a subset of these cells, which was confirmed with flow cytometry of the tumor. Although the patient had no preceding patch or plaque stage, the authors herein report this extremely rare case of CD4/CD8 dual-positive peripheral T-cell lymphoma, not otherwise specified presented as MF d'emblée and discuss the seldom similar cases published previously.